PERANCANGAN APLIKASI PENJUALAN SOUVENIR PESTA PERNIKAHAN BERBASIS WEB DENGAN MENGGUNAKAN PHP - Mintorogo, Dwi Anggadi; Saputra, Deni (Sekolah Tinggi Teknologi 10 Nopember, 2018)
The development of information and communication technology currently has a big influence on various aspects of life, even human behavior and activity is now much dependent on information and communication technology. With the various advantages and convenience it offers will certainly improve the computerization and effectiveness of the work of a company. One of the advantages of a computerized system is to produce information that is relevant, timely and accurate. The resulting information can not be separated from good information management and able to maintain the smoothness of information needs in the circulation of data of a system. With this online store, facilitate the prospective buyers to find information of goods without having to come to the seller's location. Operating costs are relatively minimal, in contrast to opening a conventional store that must rent a place with an expensive price. Online stores can be handled whenever and wherever. Has a wide range of markets, because it can reach any area as long as there is internet connection and also can operate without time constraints, there is even an online store that is open 24 hours nonstop.